On the appeal to exemplatiry and the insertion of the exemplum in XIV century texts : the case of the Gran Crónica de Alfonso XI and the Crónica de Pedro I y Enrique II of Pero López de Ayala - Érica Janin (Estudios de Historia de España, 2017)
It is undisputable that the study of the insertion of the exemplum in the corpus of medieval texts has recently acquired an enormous and well-deserved importance. However, the researches have trimmed the object of study in a fragmentary way, and the consequence is a proliferation of works on the exemplum, which results in a lack of studies on exemplarity in a broader sense, inclusive of the exemplum but also of other textual formats and resources. I will aim to review in a brief and summary way some titles from the current bibliography on the exemplary matter, not with the purpose of evaluating exhaustively or completely all the contributions on the subject (a task that appears to be excessive because of the copiousness of the studies regarding the issue) but with the intention of surveying critical and theoretical tendencies in that bibliography, representative of the approaches in vogue. Also, I aspire to lay the foundations of a critical approach to further our knowledge of exemplary tales in the strict sense and exemplarity in a broad sense. This will enable us to include as corpus for its study other textual formats that, while not being strictly exempla, serve as vehicles of exemplarity: prophecy, legend, fazaña, etc.